El contrato de trabajo y la aplicación del principio de protección en la remuneración - Johnatan Fabricio, Vilema Angos (2021)
ABSTRACT The protection of the right to work and the workers' rights; are fundamental obligations that the Ecuadorian State must guarantee to citizens. One of the workers' rights is to receive a living wage that allows him to improve his living conditions; the worker's remuneration for his legal and legal work is fundamental for personal and family development. However, some cases and employers do not respect the rules and pay their workers and honorary employees, which do not reach them to cover basic needs. This problem served as the basis for carrying out this research entitled: THE WORK CONTRACT AND THE APPLICATION OF THE PRINCIPLE OF PROTECTION IN REMUNERATION, whose purpose was to describe through the case study and the principle of protection was observed in The employment contracts to guarantee a remuneration according to the Law, to reach the achievement of the general objective, a legal, doctrinal, and critical study of the employment contracts, labor policies, the principle of protection, and the Law was carried out to fair remuneration. The research analysis unit is located in the city of Riobamba, specifically in the Labor Inspectorate. To determine if the individual employment content in these contracts applies the principle of protection about remuneration analyzed. Being socio-legal research, the approach is qualitative, documentary-bibliographic, essential, analytical, and descriptive; non-experimental design. For the analysis of the object of study, the inductive, analytical and descriptive method was applied. The population involved is constituted by judges guaranteeing constitutional rights, labor inspectors, workers, and employers. The questionnaire was used as an information collection instrument. The results allow us to conclude by pointing out that national and international favorable Laws protect the right to work and workers' rights. However, the protective principle is not guaranteeing the worker a fair remuneration that allows workers to live a decent life. Keywords. - Right to work, workers' rights, employment contracts, the principle of protection, remuneration. Reviewed by: Ms.C. Ana Maldonado León ENGLISH PROFESSOR C.I.0601975980